Analysis of Factors Influencing Risky Sexual Behavior among Male Students - Trisnarizki, Leonardo; Tampubolon, Rifatolistia; Nusawakan, Arwyn Weynand; Letelay, Pieter Bleriof (Journal of Language and Health, 2024)
The adolescent period is characterized by rapid growth and development, which often promotes curiosity and a quest for challenges. This lack of knowledge often results in risky sexual behaviors, which are sexual acts that can lead to pregnancy outside of marriage or sexually transmitted diseases. This study aims to identify the relationship between the role of parents, the use of information media, social norms, religion, and knowledge with risky sexual behavior in male students of Satya Wacana Christian University. This study uses a quantitative method with a cross sectional approach on male students aged 18-24 years at Satya Wacana Christian University, with 372 respondents selected using quota sampling technique. Data were collected using a questionnaire that covered various factors related to risky sexual behavior, such as parental role factors, knowledge, religion, media use, and social norms. All data were analyzed using univariate and bivariate analysis A significant relationship was not found between the role of parents, the use of information media, social norms, and knowledge with risky sexual behavior. However, there was a significant relationship between religious factors and risky sexual behavior, with a p value of 0.001. This study is hopefully able to provide a reference for further research, especially in the context of qualitative research.